Congenital rubella syndrome prevalence at seventeen Peruvian Hospitals, 1998-2000 - Blitchtein-Winicki, Dora (2002)
Objective: To determine congenital rubella syndrome (CRS) presence in Peru. Design: Descriptive, cross sectional study. Material and Methods: Review of clinical records of children hospitalized between January 1998 and June 2000 at 17 hospital pediatric services in seven districts of Peru, children who presented al least one of the following diagnosis: congenital cataracts or glaucoma, retinitis pigmentosa, congenital cardiac malformation or neurosensorial deafness. The cases were classified as suspected, probable and confirmed. Results: From 91102 hospital discharge diagnosis of children less than 12 year-old, 361 fulfilled inclusion criteria; 51,8% were suspicious, 9,7% probable, and 1,4% confirmed; 93,6% had congenital heart symptomatology, 29,6% central nervous alterations, and 18,6% ocular manifestations;11% of the children had at least two clinical manifestations. Conclusion: There is evidence of CRS in children hospitalized at 17 hospitals in Peru.